DINAMIKA KOMUNIKASI POLITIK PADA PEMILIHAN PRESIDEN DI INDONESIA - rani, samsul (UIN Antasari Banjarmasin, 2019)
The dynamics of political communication have occurred through phenomena before and after the presidential election in Indonesia, both conducted by political elites, party supporters, and the public to win the presidential candidates and vice-presidential candidates he supports. This can be seen from the form of political communication in the campaign, political attitudes in addressing the vote acquisition, and post-election political communication. Political communication through campaigns using digital media especially social media such as Twitter, Whatsapp, Facebook, Instagram, and other media has given a very significant influence in gaining public support, but negative campaigns and black campaigns (hoax) cannot be avoided, even to the legal sphere. Political communication at the end of the voting is stated through a victory speech through political speeches based on different survey results, namely quick count and exit poll. The speech added to the polemic about the validity and honesty in the implementation of the General Election because of the very significant difference in votes in Indonesia. Political communication on the determination of the results of the real count resulted in an unelected presidential candidate bringing the case to the realm of law namely the Constitutional Court court to cancel the victory of the elected presidential candidate. Political communication after the determination of the results of the elected election is that the elected president reconciles the non-elected presidential candidates to eliminate friction in the community. Besides, the coalition party supporting the elected president lobbied both fellow supporters and the elected president to get a ministerial position in the cabinet and the parliament.